Stable isotope labeling for detection of ozonation byproducts in effluent organic matter with FT-ICR-MS. (1st February 2023) - Jennings, Elaine K.; Sierra Olea, Millaray; Kaesler, Jan Michael; Hübner, Uwe; Reemtsma, Thorsten; Lechtenfeld, Oliver J.
Highlights: EfOM was ozonated with mass labeled ozone to generate mass labeled OBPs. 929 labeled OBPs were detected with FT-ICR-MS, some undetectable without 18 O. 18 O/ 16 O intensity ratios distinguish direct oxygen transfer products from indirect. OBPs were fragmented with FT-ICR-MS/MS and screened for indicative neutral losses. Functional group reactivity indicates reduced sulfur present prior to ozonation. Abstract: Despite effluent organic matter (EfOM) being a major consumer of ozone during wastewater treatment, little is known about ozonation byproducts (OBPs) produced from EfOM. To unambiguously identify OBPs, heavy ozone was used to ozonate EfOM, resulting in 18 O labeled and unlabeled OBPs. Labeled OBPs mostly represent a single 18 O transfer and were classified as either direct or indirect OBPs based on the 18 O/ 16 O intensity ratios of the isotopologues. Of the 929 labeled OBPs, 84 were unequivocally classified as direct OBPs. The remainder suggest a major contribution by indirect, hydroxyl radical induced formation of OBPs in EfOM. Overall, labelled OBPs possess a low degree of unsaturation and contributed most to OBP peak intensity – marking them as potential end products. A few direct and indirect OBPs with high peak intensity containing 18 O and heteroatoms (N, S) were fragmented with CID FT-ICR-MS/MS and screened for indicative neutral losses carrying heavy oxygen. The neutral loss screening was used to detect the 18 O location on the OBP and indicate the original functional group in EfOM based on known reaction mechanisms. We identified sulfoxide and sulfonic acid functional groups in selected OBPs – implying the presence of reduced sulfur in EfOM molecules – while no evidence for nitrogen containing functional groups reacting with ozone was found. Graphical abstract: Image, graphical abstract